(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2017)
Hortun-1 is one of the richest fossil floras of Armenia and dates from Early Pliocene (Early Akchagil). The studied material includes more than 2100 samples kept in the Institute of Botany of NAS RA, in the Palaeobotanical storage. As a result of the study, 4 imprints of leaves of Brassaiopsis mirabilis Kol. were determined, which were the first brought for the fossil floras of Hortun and for the whole Armenia. Samples give an opportunity to make a conclusion on climate change.